Project Report on Image Compression using Wavelet Tranformation JPEG-2000 - JAYAPRABA S HIREMATH (2006)
INTERNAL GUIDE: SWARNALATHA R RAO, MVJCE EXTERNAL GUIDE: BHIMSEN G V, CEO OF CITL
Keywords: Tranformation JPEG-2000